FACTORS INFLUENCING HUMAN CAPITAL DEVELOPMENT: EXPLORING THE ROLES OF BUSINESS PARTNERSHIP WITH THE NGOS AND PRIVATE SECTORS - Lladoni, Roland L.; Recio, Elizabeth O. (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
Human capital development (HCD) is vital to socio-economic development, as it equips individuals with the skills and competencies necessary for meaningful participation in the labor market. In the Philippines, a persistent mismatch between job requirements and available talent continues to contribute to unemployment and underemployment, reflecting structural gaps in education, skills training, and workforce readiness. While partnerships between non-government organizations (NGOs) and the private sector (PS) are widely promoted as mechanisms to address these gaps, existing studies remain largely descriptive and provide limited empirical evidence on which partnership factors most effectively drive HCD outcomes in developing-country contexts, particularly from both NGO and PS perspectives. To address this gap, this study examines the factors influencing the effectiveness of NGO–PS partnerships in promoting HCD in the Philippine setting. Using a mixed-methods approach grounded in an Exploratory Sequential Design, the research integrates quantitative data from semi-structured surveys conducted with 77 organizations—comprising NGOs and PS entities—with qualitative insights from key informant interviews. Regression and moderation analyses reveal that partnership effectiveness is positively associated with long-term sustainability and social and community impact. In contrast, talent acquisition and corporate social responsibility exhibit complex and non-linear dynamics, suggesting potential resource competition or misaligned organizational priorities. While diminishing returns are observed at higher levels of engagement, partnership maturity emerges as a strong predictor of successful HCD initiatives. The findings demonstrate that effective partnerships yield tangible benefits, including geographic expansion, diversification of financial resources, and strengthened organizational capacity. Businesses contribute as funders, technical experts, and policy advocates, while NGOs leverage grassroots networks to enhance community engagement and program delivery. Persistent challenges—such as communication gaps, short-term corporate commitments, and logistical constraints in remote areas—underscore the importance of institutionalizing partnerships and aligning initiatives with community needs. Overall, the study highlights the potential of strategic, well-aligned NGO–PS partnerships to strengthen employment outcomes and support inclusive, long-term socio-economic development in the Philippines.